2018
DOI: 10.1186/s12884-018-1839-5
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and depressive symptoms during pregnancy among Latina women: a prospective cohort study

Abstract: BackgroundLatina women are at increased risk for antenatal depressive disorders, which are common during pregnancy and are associated with elevated risk for poor maternal health and birth outcomes. Physical activity is a potential mechanism to reduce the likelihood of depressive symptoms. The purpose of the study was to assess whether total and domain-specific physical activity in early pregnancy reduced risk for elevated antenatal depressive symptoms in mid-late pregnancy in a population of Latina women at hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 51 publications
0
14
0
1
Order By: Relevance
“…The results of epidemiological studies from a number of countries have confirmed beneficial effects of physical activity during pregnancy on the mother's and child's health [1,2]. Regular physical exercises were shown to have a positive impact on cardiovascular endurance, lower the risk of excessive body weight gain [3], relieve spinal pains, and reduce depressive symptoms during pregnancy [4] and after childbirth as well as contribute to regaining proper body weight after childbirth. Increased physical activity during pregnancy is also associated with a lower risk of caesarean delivery [5], respiratory diseases, and macrosomia in newborns.…”
Section: Introductionmentioning
confidence: 93%
“…The results of epidemiological studies from a number of countries have confirmed beneficial effects of physical activity during pregnancy on the mother's and child's health [1,2]. Regular physical exercises were shown to have a positive impact on cardiovascular endurance, lower the risk of excessive body weight gain [3], relieve spinal pains, and reduce depressive symptoms during pregnancy [4] and after childbirth as well as contribute to regaining proper body weight after childbirth. Increased physical activity during pregnancy is also associated with a lower risk of caesarean delivery [5], respiratory diseases, and macrosomia in newborns.…”
Section: Introductionmentioning
confidence: 93%
“…Other health benefits of PA during pregnancy include relief of the symptoms of low back pain, which is very common and affects around 60% of pregnant women [22][23][24], a decrease in the likelihood of caesarian delivery and postpartum recovery time [11,[25][26][27]. Studies have also shown that physically active pregnant women have a lower chance for the development of depression and have lower anxiety levels [28][29][30][31][32]. The studies on the influence of the in utero environment show that it has effects on infants and throughout childhood into adulthood [33], which is in accordance with developmental origins hypothesis.…”
Section: Introductionmentioning
confidence: 99%
“…The authors did not observe any significant associations between healthpromoting physical activity and the presence of depressive symptoms, although they assumed that physical activity might have a potential protective mechanism against depressive symptoms. 22 The best of our knowledge, no studies on the effect of physical activity on well-being were previously performed among pregnant women undergoing amniocentesis. In our study, only 26% of women referred for amniocentesis practiced sport or participated in exercise classes such as swimming, walking, mountain hiking, jogging, prenatal exercise classes, gymnastics, and dancing classes.…”
Section: Discussionmentioning
confidence: 99%